Hepatoprotective Effect of Ethanolic Extracts of Allophylus Cobbe (L.) Raeusch leaves against Paracetamol Induced Hepatotoxicity in Albino Wistar Rats: Pharmaceutical Sciences-Pharmacy for Better Health - Chavan, Sandeep; Dias, Remeth; Magdum, Chandrakant (International Journal of Life Science and Pharma Research, 2021)
Liver disorders are one of the major concerns globally. Various conventional therapeutics used in the treatment of liver diseases are sometimes not enough and associated with serious side effects. Therefore, herbal medicines could be promising to defeat the above problems, and to treat diseases effectively. Aim of the current investigation is to screen the hepatoprotective activity of the ethanolic extract of Allophylus cobbe (EEAC) leaves against Paracetamol (PCM) induced hepatotoxicity in rats. EEAC (200 and 400 mg/kg) were administered to the rats for 7 days and hepatotoxicity was induced by administration of PCM (3 g/kg) on the 8th day. After 24 h of toxicity induction, the blood samples were collected and serum and tissue biochemical parameters like- serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transaminase (SGOT), alkaline phosphatase(ALP), acid phosphatase (ACP), Creatinine, superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), lipid peroxidation (LPO) and total proteins were analyzed. Livers of the animals were isolated and were studied for histopathological changes. The extract treated animals were compared with the animals treated with standard hepatoprotective Silymarin (100 mg/kg). Administration of PCM causes hepatotoxicity to the animals, EEAC and silymarin prevented the PCM induced hepatotoxicity. The level of the increased blood biochemical parameters were significantly decreased by oral administration of EEAC and silymarin. PCM hepatotoxicity raised the LPO activity of the liver tissue which was significantly decreased by EEAC and silymarin. Decrease in protective tissue enzymes (SOD, CAT and GSH) and the proteins by the PCM hepatotoxicity were significantly increased by the EEAC and silymarin. Histopathological observation of the PCM treated group showed the marked degeneration of the liver cells and liver damage which was significantly restored when the animals were treated with the EEAC and silymarin. Allophylus cobbe showed the presence of bioactive components in the plant having the antioxidant potential; which might be responsible for hepatoprotective activity of the plant. The present study showed that EEAC restored the levels of altered biochemical parameters and prevented the liver from the toxic effects of PCM revealing the hepatoprotective potential of Allophyluscobbe.